Influence of chronic intrauterine hypoxia on the morphofunctional features of the urinary system of fetuses and newborns - Myroshnychenko M.S.; Markovsky V.D.; Sorokina I.V. (Морфологія, 2013)
Chronic intrauterine hypoxia is one of the main factors that affects the urinary system organs of fetuses and newborns. The purpose of this study was to identify the morphofunctional features of kidneys, ureters and urinary bladder in fetuses and newborns exposed to the influence of chronic intrauterine hypoxia. The material of this study was the tissue of kidneys, ureters and urinary bladder of fetuses and newborns, which was studied using different histological and histochemical staining methods. In the study conducted by the authors in organs of urinary system of fetuses and newborn, exposed to chronic intrauterine hypoxia, identified various morphological changes, which can lead to the development of various pathologies of such system in these children in future ontogenesis.